The Changing Façade of India’s IT Sector Amidst Technological Advancement And US’ Protectionism Policies - Indras Ghosh (Journal of International Conference Proceedings (JICP), 2018)
The IT sector, one of India’s fastest growing sectors, plays a crucial role contributing to the overall economic growth of the country. Despite its seemingly healthy growth, the IT sector is facing looming challenges. While the industry relentlessly moving towards digital technologies, India’s IT sector still relies heavily on traditional IT support services such as application development and maintenance, and IT infrastructure. With India’s main trading Nation in IT sector, the US, continues to adopt inward policies to tackle its own rising unemployment rates, for the Indian IT sector the proverbial winter is coming, it seems. We will be looking at the recent global IT trends, US Government policy changes and its affect on the top 4 IT company in India; Tata Consultancy Services, Cognizant, Infosys, and Wipro. Keywords: IT Sector, US polices, service sector, product innovation, technological change